2005
DOI: 10.1099/jmm.0.46122-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Helicobacter DNA present in human colorectal adenocarcinomas by 16S rDNA PCR amplification and pyrosequencing analysis

Abstract: Seroepidemiological studies have indicated that Helicobacter pylori infection might be a possible risk factor for colorectal adenocarcinoma (CRC) development. However, limited information is available as to whether or not Helicobacter species are present in CRC tissues. In this study the presence of Helicobacter DNA in 77 CRC biopsies was investigated by means of a Helicobacter species-specific 16S rDNA PCR assay and real-time DNA pyrosequencing of the 16S rDNA variable V3 region. Pyrosequencing revealed the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 34 publications
2
45
0
Order By: Relevance
“…Some studies were able to identify the genetic material of the bacteria in colonic neoplasias (3,8,15) . The effect of the intestinal flora as a carcinogenic agent has been evaluated and the possibility exists that bacteria such as H. pylori circulating in the intestines could directly activate carcinogenesis (33) .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies were able to identify the genetic material of the bacteria in colonic neoplasias (3,8,15) . The effect of the intestinal flora as a carcinogenic agent has been evaluated and the possibility exists that bacteria such as H. pylori circulating in the intestines could directly activate carcinogenesis (33) .…”
Section: Resultsmentioning
confidence: 99%
“…Like serologic studies, studies using PCR methods have been equivocal. Two studies found that detection of H. pylori via PCR was significantly higher in colorectal adenocarcinoma tissues compared with normal colorectal tissues (Grahn et al, 2005;Jones et al, 2007), but a third study found that only 1.2% of malignant colorectal tissue samples were positive for H. pylori, compared with 6% of normal tissues (Bulajic et al, 2007). The 13C-urea breath test has 97% sensitivity and specificity in H. pylori detection (Chen et al, 2003); however, as in PCR-based studies, the evidence is not convincing.…”
Section: Discussionmentioning
confidence: 98%
“…Recent reports suggest that H. pylori may be an association factor involved in the development of colorectal cancer in patients infected with certain strains (9,10). The Swedish group of Grahn et al (11) was the first who previously described the potential molecular identification of Helicobacter DNA in colorectal cancer biopsies by means of a 16S rDNA PCR amplification assay combined with pyrosequencing analysis. Furthermore, Maggio-Price et al (12) proved that infection of SMAD3 À/À mice with Helicobacter triggers colon cancer in 50% to 66% of those animals.…”
Section: Introductionmentioning
confidence: 99%